Analysis of E-Learning Commitment-Making Officer for the Effectiveness of Implementation of the Expenditures Budget Working Unit Ministry/Institution in Indonesia - Achmat Subekan; Ali Said; Luthfi Nurdiansyah; Ahmad Khusnadi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study aims to determine the effect of Commitment-Making Officer Elearning (PPK) on the effectiveness of the budget implementation of working units managing the State Budget (APBN) in ministries and agencies. The training organized by the Budget and Treasury Education and Training Center is intended to respond to the Covid-19 Pandemic and demands for increased Commitment-Making Officer competencies. The formulation of the research problem raised is bwhat is the influence of motivation, training tools, and learning methods on the performance of budget execution, either partially or simultaneously. The research method used is a mixed method. Quantitative data was obtained through a questionnaire which was delivered to the participants and then processed Statistical Product and Service Solutions (SPSS). Meanwhile, qualitative data was obtained through in-depth interviews with informants or resource persons. The results of the study show that Commitment-Making Officer e-learning is effective in improving the performance of budget execution in the participating working units . From the variables studied, effectiveness is proven by the significant influence of motivation, training tools, and learning methods on the performance of participants in implementing the budget. The effectiveness of such influence is mediated and strengthened by the understanding that results from learning. Of the three independent variables, motivational variables have the greatest influence on performance, both directly and indirectly. As an intervening variable, understanding has the strongest influence on performance when compared to motivation, tools, and methods.